Mycotoxin detection in poultry feeds and raw materials employing different methods - JAND, S K; SINGH, P P (The Indian Journal of Animal Sciences, 2013)
Samples (332) of poultry feeds and raw materials were screened for mycotoxins; 66.8% revealed different mycotoxins from 50-1000 ppb. Mycotoxins detected from the samples in decreasing order were aflatoxins, ochratoxins, citrinin and sterigmalocystine, either alone or in combination. Bright greenish yellow (BOY) fluorescence, pressure minicolumn (PMC) , thin layer chromatography mC) and multiple sEreening methods were used for mycotoxin detection. Pressure minicolumn (PMC) and thin layer chromatography methods were more sensitive than the other methods.